Plasma nicotine levels after cigarette smoking and chewing nicotine gum. Issue 6017 (1st May 1976) - Russell, M A; Feyerabend, C; Cole, P V
Abstract : Plasma nicotine levels were measured over seven hours of smoking cigarettes (1-2 mg nicotine) in a single subject under standardised conditions, and were compared with the levels obtained from chewing-gum containing either 2 mg or 4 mg nicotine. Levels comparable to those resulting from smoking were not obtained with the 2-mg gum, but peak levels on the 4-mg gum averaged 40-1 ng/ml from the third gum onwards compared with 49-2ng/ml after cigarettes. Nicotine was absorbed much more slowly from the gum than from cigarettes. It took 15-30 minutes for the 4-mg gum to raise the plasma nicotine by an average of 11-9 ng/ml compared with an average increase of 27-8 ng/ml within two minutes of completing each cigarette. In a sample of 15 smokers attending a withdrawal clinic the average plasma nicotine concentration while taking 2-mg nicotine chewing-gum was only 10-8 ng/ml compared with 30-4 ng/ml two minutes after smoking a cigarette. Although plasma nicotine levels equivalent to those following cigarette smoking may be obtained by chewing at least 10 pieces of 4-mg nicotine gum daily, the slower rate of absorption may limit its therapeutic value as a substitute for cigarette smoking.